AN AN ANALYSIS OF REALITY, NEUROTIC, AND MORAL ANXIETY IN DON’T BREATHE FILM - Elvyno, Andreas; Al-Baroroh, Aisyah (Linguistics and Literature Journal, 2025)
This article analyzes the depiction of anxiety in the Don’t Breathe, focusing on the types of anxiety experienced by the characters, Rocky and Alex. Using Calvin Hall’s theory of anxiety (1954), the research identifies three key forms of anxiety portrayed in the film: reality anxiety, neurotic anxiety, and moral anxiety. Reality anxiety manifests through the characters’ fear of real external dangers, such as getting caught or physical harm. Neurotic anxiety reflects their internal conflicts and fears about losing control over instincts and impulses. Moral anxiety reveals their feelings of guilt and shame related to the ethical implications of their actions. Employing a qualitative approach, this article examines how these anxieties shape the characters’ decisions and behaviours in a high-pressure, life-threatening situation. The film’s use of setting, cinematography, and narrative techniques intensifies the portrayal of anxiety, immersing viewers in the characters’ psychological struggles. This analysis contributes to a deeper understanding of how psychological theories of anxiety can be applied in film studies to explore complex character experiences and enrich narrative meaning. Keywords: anxiety, Don’t Breathe, moral anxiety, neurotic anxiety, reality anxiety